2008
DOI: 10.1159/000142046
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics of Respiratory Allergy in Immigrants in Northern Italy

Abstract: Background: Respiratory allergy is influenced and determined by genetic and environmental factors. Migration is a good epidemiological model to indirectly assess the influence of the environment. We assessed the clinical characteristics of respiratory allergy in immigrants in Brescia, Italy. Methods: We prospectively collected the data of all immigrants referred to our allergy service for respiratory complaints since 1992. All patients underwent a standard diagnostic workup. The records of a matched Italian po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Migration studies provide useful information on the role of environmental factors, including climate changes, and on the development of atopy and asthma [48][49][50][51]. Migration involves exposure to a new set of air pollutants and allergens, as well as changes in housing conditions, diet and accessibility to medical services, all of which are likely to affect migrants' health.…”
Section: Role Of Migration Studiesmentioning
confidence: 99%
“…Migration studies provide useful information on the role of environmental factors, including climate changes, and on the development of atopy and asthma [48][49][50][51]. Migration involves exposure to a new set of air pollutants and allergens, as well as changes in housing conditions, diet and accessibility to medical services, all of which are likely to affect migrants' health.…”
Section: Role Of Migration Studiesmentioning
confidence: 99%
“…In a recent survey, we collected the data of 237 adult immigrants (129 women, 108 men; mean age, 36.4 years; age range, 18-54 years) living in Brescia, Northwest Italy[19]. The data were compared with a matched sample of the local population.…”
Section: "Immigrant-united Airways Disease": a New Phenotype Of Respimentioning
confidence: 99%
“…The prevalence of asthma symptoms increased with increases in the number of years living in Italy, suggesting that exposure to environmental factors may contribute to the development of asthma in childhood. The prevalence of respiratory symptoms was lower in migrant children than in children born in Italy, and the prevalence increased with the number of years living in Italy [21] . However, a more recent study did not show significant differences in respiratory allergic diseases in immigrant children born either in Italy or abroad compared to children born to Italian parents [23] .…”
Section: Introductionmentioning
confidence: 82%
“…More recent studies of immigrants to Italy confirmed that environmental factors functioned in the induction of upper and lower respiratory allergies more so than genetic factors that were a further promoting factor [20][21][22] . Migrant children had a lower prevalence of asthma symptoms than children born in Italy.…”
Section: Introductionmentioning
confidence: 99%